초고령 결직장암 환자들에서 복강경 절제술의 단기 결과 - 정원범; Won Beom Jung; 신진용; Jin Yong Shin; 서병조; Byoung Jo Suh (The Korean journal of gastroenterology, 2017)
Background/Aims: Due to the recent increase in elderly population, laparoscopic surgery is more frequently performed in the elderly. This study aimed to compare the short-term outcomes of laparoscopic colorectal cancer surgery between the very elderly group (VEG), categorized as those with age over 80 years and the elderly group (EG), categorized as those with age 65 to 79 years. Methods: We retrospectively compared 48 very elderly patients with 96 elderly patients (1:2 matched) who underwent laparoscopic resection for colorectal cancers at our institution between March 2010 and December 2014. The clinicopathologic parameters, surgical characteristics and short term outcomes were compared. Results: There was no statistically significant difference in clinicopathologic characteristics between VEG and EG. Postoperative pain score (7 points vs. 6 points, p=0.264), time to first flatus (3 days vs. 3 days, p=0.335), hospital stay (15 days vs. 16.5 days, p=0.361), complication rates (47.9% vs. 26.0%, p=0.147) and major complication rate (25% vs. 20.8%, p=0.681) were not statistically different between the two groups. Before surgery, VEG had higher rate of neurologic underlying disease, such as dementia or cerebrovascular disease, than EG (25.0% vs. 7.3%, p=0.007). Conclusions: There was no significant difference in the clinicopathologic characteristics, short-term outcomes, and complication rates for laparoscopic colorectal resection between VEG and EG, except delirium. Age over 80 years may be relevant for the application of laparoscopic colorectal cancer resection. (Korean J Gastroenterol 2017;69:291-297)